Efeitos dos níveis de desigualdade e pobreza sobre a taxa de crescimento dos estados brasileiros (1987-2002) - Barros, Américo Cardoso Soares de (2006)
Brazil is well-known by elevated indexes of inequality distribution and high levels of poverty, which makes us to ask if those factors have effects on economic growth. This work aims to observe the effects of inequality and poverty on economic growth in Brazil during the period 1987 - 2002. The empirical model presented is estimated from a panel dataset from Brazilian States, using Generalized Least Squares - GLS. The proposed model is estimated considering different periods, in a way that is possible to obtain the mean of the growth rate from each period, and the initial value of the independent variables in each period. The results allow us to conclude that the income inequality, in general, has a positive and significant effect on economic growth in Brazil, and the effect of variables as poverty and indigence varies according to the regions and periods that are analyzed. A trend to the conditional convergence was also concluded where the tax of growth of the per capita income is related inversely the changeable initial per capita income when it considers 2 periods of 8 years. However the educational variable if show significant and positives, being in accordance with evidences in literature.